2013
DOI: 10.1371/journal.pone.0054781
|View full text |Cite
|
Sign up to set email alerts
|

Women with Multiple Chemical Sensitivity Have Increased Harm Avoidance and Reduced 5-HT1A Receptor Binding Potential in the Anterior Cingulate and Amygdala

Abstract: Multiple chemical sensitivity (MCS) is a common condition, characterized by somatic distress upon exposure to odors. As in other idiopathic environmental intolerances, the underlying mechanisms are unknown. Contrary to the expectations it was recently found that persons with MCS activate the odor-processing brain regions less than controls, while their activation of the anterior cingulate cortex (ACC) is increased. The present follow-up study was designed to test the hypotheses that MCS subjects have increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Within the vmPFC, more in particular the sgACC, this area is related to arousal processes and implicated in a corticolimbic neurocircuit associated with ‘visceromotor’ functions playing an important role in modulating affect, such as sadness activation and ruminative thought patterns [47]. This functional amygdala - sgACC coupling has also been reported in female anxiety patients scoring higher than controls on HA [48]. However, our findings seem to be in disagreement with the study of Kim and colleagues [13] where reverse amygdala –vmPFC FC results were reported in relation to higher scores on the State and Trait Anxiety Inventory self-report questionnaires (STAI-S, STAI-T [49]).…”
Section: Discussionmentioning
confidence: 77%
“…Within the vmPFC, more in particular the sgACC, this area is related to arousal processes and implicated in a corticolimbic neurocircuit associated with ‘visceromotor’ functions playing an important role in modulating affect, such as sadness activation and ruminative thought patterns [47]. This functional amygdala - sgACC coupling has also been reported in female anxiety patients scoring higher than controls on HA [48]. However, our findings seem to be in disagreement with the study of Kim and colleagues [13] where reverse amygdala –vmPFC FC results were reported in relation to higher scores on the State and Trait Anxiety Inventory self-report questionnaires (STAI-S, STAI-T [49]).…”
Section: Discussionmentioning
confidence: 77%
“…However, our findings revealed an opposite direction of associations in which higher HA was correlated with less‐efficient CPM responses. Previous studies indeed reported that high activity in the serotonergic system characterized individuals with high HA, however, others did not find these relationships . Furthermore, one study reported findings in the opposite direction: low basal levels of central serotonin were related to higher HA scores .…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies indeed reported that high activity in the serotonergic system characterized individuals with high HA, 41-44 however, others did not find these relationships. [45][46][47] Furthermore, one study reported findings in the opposite direction: low basal levels of central serotonin were related to higher HA scores. 48 Additionally, use of tricyclic antidepressants (TCA) or selective serotonin reuptake inhibitors (SSRI) was followed by reduction in HA scores in studies of patients with depression and generalized anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The relative FDG uptake increase found in the present study in MCS patients OLF at rest when compared to HC is in line with those theories assessing CNS hypereactivity and limbic kindling as key nodes in pathophysiological underpinnings of MCS (Bascom et al 1997;Winder 2002). Agreeing with those arguments suggesting both attention bias and over-ridden neural behaviour to chemical exposure in MCS patients (Andersson et al 2009;Witthöft et al 2006;Winder 2002), this finding could depict for the first time a subcortical resting state correlate of hyper-sensitized neural structure before reaching those secondary/associative olfactory ones (such as OFC, PHG) in which emotional/affective/over-attentional processes could be residing (Qureshy et al 2000;Kroupi et al 2012;Keller 2011) and secondary MCS disease-related processes could be nestled (Hillert et al 2007;Orriols et al 2009;Hillert et al 2013). Further, these data appear more relevant especially when merged with the wider FDG uptake found at rest in frontal-prefrontal cortex and ACC in the same sample of HC subjects with respect to the same sample of MCS patients (Chiaravalloti et al 2015).…”
Section: Discussionmentioning
confidence: 65%